In-silico investigation of phenolic compounds from leaves of Phillyrea angustifolia L. as a potential inhibitor against the SARS-CoV-2 main protease (Mpro PDB ID:5R83) using a virtual screening method - Ahmed Boufissiou; Mohnad Abdalla; Mohamed Sharaf; Saud I. Al-Resayes; Kadi Imededdine; Mahboob Alam; Sakina Yagi; Mohammad Azam; Mohamed Yousfi (Journal of Saudi Chemical Society, 2022)
There is currently a global COVID-19 pandemic caused by the severe acute respiratory syndrome Coronavirus-2 (SARS-CoV-2) and its variants. This highly contagious viral disease continues to pose a major health threat global. The discovery of vaccinations is not enough to prevent their spread and dire consequences. To take advantage of the current drugs and isolated compounds, and immediately qualifying approach is required. The aim of our research is evaluation the potency for natural antiviral compounds against the SARS CoV-2 Mpro. Molecular docking of four phenolic compounds from Phillyrea angustifolia leaves with SARS-CoV-2 Mpro has been conducted. Similarly, the stability of selected ligand–protein interactions has been determined using MD simulations. Moreover, the quantitative structure–activity relationship (QSAR), MMGBSA binding energies, pharmacokinetics, and drug-likeness predictions for selected phenolic have been reported. The selected phenolic compounds (Luteolin-7-O-glucoside, Apigenin-7-O-glucoside, Demethyl-oleuropein, and Oleuropein aglycone) revealed strong binding contacts in the two active pockets of a target protein of SARS-CoV-2 Mpro with the docking scores and highest binding energies with a binding energy of −8.2 kcal/mol; −7.8 kcal/mol; −7.2 kcal/mol and −7.0 kcal/mol respectively. Both Demethyloleoeuropein and Oleuropein aglycone can interact with residues His41 and Cys145 (catalytic dyad) and other amino acids of the binding pocket of Mpro. According to QSAR, studies on pharmacokinetics and drug-like properties suggested that oleuropein aglycone could be the best inhibitor of SARS-CoV-2 for new drug design and development. Further in vivo, in vitro, and clinical studies are highly needed to examine the potential of these phenolic compounds in the fight against COVID-19.